1999
DOI: 10.1111/1468-2427.00193
|View full text |Cite
|
Sign up to set email alerts
|

Informal Spaces: The Geography of Informal Economic Activities in Brussels

Abstract: This paper unravels the relations between different categories of the informal economy and their spatial distribution in the geographical setting of Brussels. Micro perspectives (households as economic agents) and macro perspectives (the informal economy related to economic recession) are combined in order to deal with categories of informal activities which are homogenous in terms of their spatial logic. In the first part we review several classifications of informal economic activities and assess them in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 7 publications
0
82
0
5
Order By: Relevance
“…On the one hand, there has been a long-standing belief at all spatial scales that the undeclared economy is more prevalent in poorer areas. This is viewed as the case whether one is discussing global regions [4,17], variations between nations [14,18], local and regional variations [9,16] or urban-rural variations [19,20]. On the other hand, groups that are relatively marginalised from the formal labour market are also believed to be more likely to work in the undeclared economy.…”
Section: Competing Perspectives On Who Engages In Undeclared Workmentioning
confidence: 99%
“…On the one hand, there has been a long-standing belief at all spatial scales that the undeclared economy is more prevalent in poorer areas. This is viewed as the case whether one is discussing global regions [4,17], variations between nations [14,18], local and regional variations [9,16] or urban-rural variations [19,20]. On the other hand, groups that are relatively marginalised from the formal labour market are also believed to be more likely to work in the undeclared economy.…”
Section: Competing Perspectives On Who Engages In Undeclared Workmentioning
confidence: 99%
“…Over the past decade or so, a number of studies have shown that the size of the shadow economy is not evenly distributed but rather, varies across not only global regions (ILO, 2013), cross-nationally (Putni š and Sauka, 2012Sauka, , 2013Sauka, , 2014aSchneider, 2013;Schneider and Williams, 2013;Williams, 2014bWilliams, ,c, 2015b) and locally and regionally (Kesteloot and Meert, 1999;Williams and Windebank, 2001), but also according to various socio-demographic and socio-economic variables such as gender (ILO, 2013;Leonard, 1994Leonard, , 1998St nculescu, 2005), age (Pedersen, 2003), employment status (Brill, 2011;Leonard, 1994;Slavnic, 2010;Taiwo, 2013) and income level (Barbour and Llanes, 2013;Williams, 2004). The consequence has been that a more contextualised understanding has emerged which recognises how the shadow economy can be large and growing in some populations, but smaller and declining in others (Pfau-Effinger, 2009;Putni š and Sauka, 2014a,b;Sepulveda and Syrett, 2007;Williams, 2013Williams, , 2014bWilliams, ,c,2015a.…”
Section: Explaining the Shadow Economy: A Tax Morale Approachmentioning
confidence: 99%
“…Numerous studies have revealed how the prevalence of the informal economy varies not only cross-nationally (ILO, 2012;Schneider and Williams, 2013) but also locally and regionally (Kesteloot and Meert, 1999) and by employment status (Slavnic, 2010;Taiwo, 2013), age (Pedersen, 2003), gender (ILO, 2013 and income level (Barbour and Llanes, 2013;Williams, 2009). The outcome has been a more contextualised understanding which recognises how the informal economy can be large and growing in some populations, but smaller and declining in others (Pfau-Effinger, 2009;Williams and Horodnic, 2015).…”
Section: Explaining the Informal Economy: An Institutional Perspectivementioning
confidence: 99%